Pengaruh Model Problem Based Learning Berbasis Etnomatematika Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII - Ardiana, Lailik; Baidowi, Baidowi; Ulfa Lu'luilmaknun (FKIP Universitas Mataram, 2025)
This study was motivated by the low mathematical problem-solving ability of students, which is attributed to the use of ineffective, teacher-centered learning models. One approach that can be applied to improve students’ mathematical problem-solving skills is the problem-based learning (PBL) model. This study aims to determine the effect of implementing an ethnomathematics-based problem-based learning model on students’ mathematical problem-solving ability. The research was conducted at SMP Negeri 14 Mataram in the 2024/2025 academic year using a quantitative approach with a quasi-experimental design. The population consisted of all eighth-grade students at SMP Negeri 14 Mataram. The research sample comprised 60 students, with 30 students in the experimental class and 30 in the control class, selected through simple random sampling. The data collection instrument was a mathematical problem-solving test. The average score of the experimental class was 77.70, which was higher than the control class’s average score of 71.40. The analysis results showed that . Furthermore, the effect size calculation yielded d = 0.69, indicating a moderate effect. These results show that the ethnomathematics-based problem-based learning model positively influences the mathematical problem-solving ability of eighth-grade students at SMP Negeri 14 Mataram, particularly in the topic of circles.